Participatory Action Research: Preservation of Sacred Rice and Cultural Resilience in the Lower Paramasan Dayak Community - Dyah Febria Wardhani; Deasy Arisanty; Siti Faizah; Muhammad Siddik (Borneo Research and Education Center, 2026)
Beras Keramat, a local rice variety with high cultural and spiritual value, faces an imminent threat of extinction due to declining cultivation and shifting agricultural priorities. This study aims to revitalize the preservation of Beras Keramat and enhance community food security through a participatory approach. Conducted over a two-month period in Paramasan Bawah Village, this research utilizes the Action Research model, consisting of a cyclical process of Planning, Acting, Observing, and Reflecting. Data were collected through in-depth interviews and field observations involving 9 key informants. This research utilizes the Action Research model, consisting of a cyclical process of Planning, Acting, Observing, and Reflecting. The intervention involved a collective planting strategy in which each household was mandated to cultivate at least one gantang of seeds, accompanied by documentation of traditional rituals and monitoring of youth engagement. The findings indicate that the structured action cycle successfully achieved its key outcome indicators, notably increasing cultural awareness and securing a stable seed stock of Beras Keramat within the community. The integration of ritual documentation with practical cultivation served as an effective bridge for intergenerational knowledge transfer. This study develops the concept of